You need to subtract (not add) 10 to both sides of the equation. The purpose is to get the unknown quantity on one side and the known quantity on the other side.
x + 10 - 10 = -13 + (-10)
x = -23
not sure about this can someone please help me
solve for x using the addition principle
x+10=-13
Now I added 10 to both sides 10 + 10 that gives me 20
then I added -13 +10 = -3
my x is the 20 or did I mess this problem up all the way around?
2 answers
you -10 from both sides not add
[do the opposite]
so x=-23
[do the opposite]
so x=-23